Incidence of Aphid on Different Brinjal Germplasm Related to Abiotic and Biotic Factors - Yasmin, F; Amin, MR; Swapon, MAH; Hossain, MM (Bangladesh Journal of Agricultural Research, 2022)
The study was conducted with BD-7320, BD-7328, BD-9952, BD-10154, BD- 10158, BARI Begun-1, BARIBegun-4, BARIBegun-5, BARIBegun-6, BARIBegun-7, BARIBegun-8 and BARIBegun-9 germplasms of brinjal with a view to understanding the effect of temperature, relative humidity, rainfall and predators on the incidence of aphid during September 2018 to March 2019. Aphid incidence and infestation started from the last week of November and the highest incidence was recorded during 2nd week of January on BD-10154.At that week, aphid showed lower number of incidence on BARI Begun-5, BARI Begun-6, BARI Begun-8 and BARI Begun-9. The highest infestation of aphid was observed on BARI Begun-5 during 2nd week of March, when the lowest infestation was found on BD-9952. Maximum and minimum temperatures showed significant positive correlation, relative humidity (RH) and rainfall revealed non-significant correlation with aphid incidence. Aphid abundance showed highly significant positive correlation with the abundance of predators on all the tested germplasms. Bangladesh J. Agril. Res. 45(4): 371-378, December 2020